Familial Chylomicronemia Syndrome-Induced Acute Necrotizing Pancreatitis during Pregnancy - Julia Cristina Coronado Arroyo; Marcio José Concepción Zavaleta; Eilhart Jorge García Villasante; Mikaela Kcomt Lam; Luis Alberto Concepción Urteaga; Francisca Elena Zavaleta Gutiérrez (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Acute pancreatitis is a rare condition in pregnancy, associated with a high mortality rate. Hypertriglyceridemia represents its second most common cause.We present the case of a 38-year-old woman in the 24th week of gestation with a history of hypertriglyceridemia and recurrent episodes of pancreatitis. She was admitted to our hospital with acute pancreatitis due to severe hypertriglyceridemia. She was stabilized and treated with fibrates. Despite her favorable clinical course, she developed a second episode of acute pancreatitis complicated by multi-organ dysfunction and pancreatic necrosis, requiring a necrosectomy. The pregnancy was ended by cesarean section, after which three plasmapheresis sessions were performed. She is currently asymptomatic with stable triglyceride levels. Acute pancreatitis due to hypertriglyceridemia represents a diagnostic and therapeutic challenge in pregnant women, associated with serious maternal and fetal complications. When primary hypertriglyceridemia is suspected, such as familial chylomicronemia syndrome, the most important objective is preventing the onset of pancreatitis.